Microbial Fuel Cell for Dairy Waste Treatment and Electricity Generation - Chaulagain, Rosy; Maharjan, Sujeeta; Maharjan, Saru; Pradhanang Adhikari, Mandira; Joshi, Jarina (Journal of Nepal Biotechnology Association, 2026)
Observing waste as a resource sparks interest in recovering dairy wastewater for resilient sustainability. Dairy wastewater, rich in organic content, is very much suitable for microbial fuel cell (MFC) applications. This paper used MFCs to study electricity generation and dairy waste treatment with paneer whey as a substrate and a biocatalyst culture from dairy development corporation (DDC) sewage targeting for lactose-utilizing strains. Bacteria from DDC sewage found to contain Klebsiella, Pseudomonas, Salmonella, and Escherichia coli, which were identified by biochemical tests. An yeast Sungouiella pseudointermedia was identified molecularly by D1D2 primer amplification and sequencing. A dual-chamber MFC with paneer whey, a bacterial consortium from DDC sewage, and alcohol-treated CNT-coated graphite felt electrodes removed 75.71% of total reducing sugar, 61.03% COD, and 48.91% total phosphorus, generating 25.869 W/m³. A simpler MFC with paneer whey, a bacterial consortium, and 0.1 M phosphate buffer removed 95.06% of total reducing sugar, 58.27% COD, 65.67% total phosphorus and 67.13% ammoniacal nitrogen but had lower power output. Challenges like pH regulation and equipment limitations are key for optimizing MFC performance and adoption. MFCs show promise as sustainable energy recovery and wastewater treatment solutions.